7797 Characteristics of liver type 2 innate lymphocytes in blood-glucose lowering effect via IL13-IL-13R interaction through GATA3-dependent transcriptional factor network - Kozu, Ryunosuke; Fujimoto, Masanori; Taki, Yuki; Kono, Takashi; Onodera, Atsushi; Tanaka, Tomoaki (Journal of the Endocrine Society, 2024)
Abstract Disclosure: R. Kozu: None. M. Fujimoto: None. Y. Taki: None. T. Kono: None. A. Onodera: None. T. Tanaka: None. Introduction: The metabolic improving effects of type 2 innate lymphocytes (ILC2) have attracted attention in both mice and human; ILC2 was originally found as a lymphocyte population in mesenteric adipose tissue and is involved in many organs immune responses (Nature, 2010, 463,540). IL33-stimulated activated ILC2 in adipose tissue suppresses obesity (Nature, 2015, 519, 242), via IL13 production (Nature Commun., 2017, 8, 15781). In this context, we found that ILC2 in the liver exhibits a function of inhibiting gluconeogenesis via IL-13 and exerts a blood glucose-lowering effect (Nature Commun., 13, 5408, 2022). However, the regulatory mechanism of why liver ILC2 functions to improve glucose metabolism is not clarified. Here, we examined the molecular characteristics of liver ILC2 and its cell-cell interaction by single cell analysis of hepatocytes and liver ILC2 in mouse model. Method The subject was the liver and lung (for comparison) of a BALB/c mouse model in which ILC2 was activated by IL-33 administration. scRNA-seq followed by FACS sorting was performed. Cell–cell ligand–receptor interaction analysis was performed using CellPhoneDB (v.2.0.0) to document ligand–receptor analysis of cell populations in the liver, especially for assessment of the interactions between hepatocytes and ILC2. For TFs analysis, SCENIC (Single-Cell rEgulatory Network Inference and Clustering) was used. Results: IL-33 injection, an activator of ILC2, strongly stimulated liver ILC2, which in turn lead to reducing vivo blood glucose levels in accordance with gluconeogenesis inhibition. With the aim of clarifying the mechanism of action, single cell analysis revealed that ILC2 in the liver has strong IL-13 producing ability. In addition, cell-cell interaction analysis demonstrated that certain hepatocyte clusters with portal vein markers express IL-13R, and the interaction of liver ILC2 with IL-13R suppresses the expression of G6pc and Pck1 glycogenic enzymes, thereby lowering blood glucose. Finally, to address unique characteristics of liver ILC2, we performed SCENIC and found that Gata3, a key regulator of IL13, was significantly activated upon IL-33 treatment in liver ILC2 with transcriptional factor network including BATF (basic leucine zipper transcription factor, activating transcription factor-like) and AP1 family. Discussion Hepatocytes, particularly with ILC2 interaction, function differently in distinct areas due to the influx of high concentrations of nutrients from the portal vein. Thus, clarification of the relationship between GATA3 transcriptional complex mechanism and nutrients in liver ILC2 may lead to novel regulatory mechanisms and therapeutic targets for liver gluconeogenesis through immunometabolic linkage. Presentation: 6/1/2024